Integration techniques for surface X‐ray diffraction data obtained with a two‐dimensional detector. (4th February 2014) - Drnec, Jakub; Zhou, Tao; Pintea, Stelian; Onderwaater, Willem; Vlieg, Elias; Renaud, Gilles; Felici, Roberto
<x xml:space="preserve">Abstract</x> This article proposes two integration methods to determine the structure factors along a surface diffraction rod measured with a two‐dimensional detector. The first method applies the classic way of calculating integrated intensities in angular space. This is adapted to work efficiently with two‐dimensional data. The second method is based on integration in reciprocal space. An intensity map is created by converting the detected intensity pixel by pixel to the reciprocal space. The integration is then performed directly on this map. A theoretical framework, as well as a comparison between the two integration methods, is provided.